Layered high-entropy sulfides: boosting electrocatalytic performance for hydrogen evolution reaction by cocktail effects - Ling Lin; Ziming Ding; Guruprakash Karkera; Thomas Diemant; Dong-Hui Chen; Maximilian Fichtner; Horst Hahn; Jasmin Aghassi-Hagmann; Ben Breitung; Simon Schweidler (Materials Futures)
This study explores high-entropy sulfides (HESs) as potential electrocatalysts for the hydrogen evolution reaction (HER). Novel Pa -3 and Pnma structured HESs containing Fe, Mn, Ni, Co and Mo, were synthesized via a facile mechanochemical method. Structural and chemical properties were extensively characterized using x-ray diffraction, transmission electron microscopy, energy-dispersive x-ray spectroscopy, and x-ray photoelectron spectroscopy. The electrocatalytic performance of four as-prepared HESs in alkaline electrolyte for HER reveals the remarkable outperformance compared to medium-entropy and conventional sulfides. Particularly, (Fe _0.2 Mn _0.2 Ni _0.2 Co _0.2 Mo _0.2 )S _2 demonstrated outstanding activities, with minimal overpotentials (187 mV at 10 mA cm ^–2 ) and outstanding durability under harsh alkaline conditions (a mere polarization increase Δ E = 17 mV after 14 h via chronopotentiometry). The remarkable catalytic activities can be attributed to synergistic effects resulting from the cocktail effects within the high-entropy disulfide. The introduction of Mo contributes to the formation of a layered structure, which leads to an increased surface area and thus to a superior HER performance compared to other HES and conventional sulfides. This work demonstrates the promising potential of HES and underscores that further development for catalytic applications paves the way for innovative routes to new and more efficient active materials for HER catalysis.